0194 Bedtime Technology Use and New Questions for the Sleep Hygiene Index. (27th May 2020) - Mastin, D; Abu-Halimeh, N; Collins, B T; Critton, J; Henderson, M; Michelle, S; Quattom, M; Sanders, M; Moore, B; Peszka, J
Abstract: Introduction: We examined the relationship between bedtime active and passive social technology use (self and bedpartner) and daytime sleepiness/sleep. We generated questions to differentiate participants with and without bedpartners and updated passive personal, active bedpartner, and passive bedpartner social technology questions of the Sleep Hygiene Index. Methods: 327 students (age: M=19.7 years, SD=3.78) recruited through psychology courses and campus newsletters received extra credit or chances to win 25 gift cards. Participants completed demographic information, the Epworth Sleepiness Scale (ESS), the Pittsburgh Sleep Quality Index, questions regarding associated features of inadequate sleep hygiene, and the Sleep Hygiene Index. Five questions assessed active and passive social technology use, presence of a bedpartner, and awareness of bedpartner active and passive social technology use during sleep time. Results: 61.8% and 62.7% of students reported frequently or always using active and passive bedtime social technology, respectively; and 23.5% and 29.1% reported noticing a partner's active or passive use. More frequent active technology use was significantly related to greater daytime sleepiness (ESS) ( r (305)=.193, p <.05), sleep disturbances (PSQI-global: r (302)=.120, p <.05), and associated features of inadequate sleep hygiene (daytime sleepiness, worry about sleep, mood disturbance, avolition, and reduced cognition ( r (306)=.212, p <.05)). Neither passive use nor passive or active partner use was significantly related to any sleep/sleepiness variables. Conclusion: We continue to find students are frequent users of bedtime social technology which is related to daytime sleepiness, disrupted sleep, and related complaints. Passive and partner active/passive bedtime technology use may not have a significant impact on daytime sleepiness. It is possible younger participants are not good judges of passive or partner technology use or this younger population is resilient to these disruptions. Support: none